Spaces and Masculinities in Transition: The Evolution of the ethos and Multimodal Discourse of Guitarricadelafuente (Anclajes, 2026)
Guitarricadelafuente’s discursive ethos and artistic vision reveal a significant evolution within his brief discography. In his linguistic, visual and performative approaches, he moves from the rural to the cosmopolitan, from an initial bucolic innocence to an urban aesthetic characterised by radical hedonism. In this process, the artist redefines, on the one hand, his artistic identity, accompanying the aesthetic with a conscious discursive strategy to construct an alternative, deliberately corporeal masculinity. But it also allows him to explore the tension between the legacy of a folklore traditionally associated with certain masculine codes and its reinterpretation through a contemporary lens. The combination of discourse analysis with visual semiotics enables a comprehensive analysis of the work as a whole (songs, music videos and other paraphonographic elements) to identify the key elements of his unique multimodal poetics.
Keywords: Discourse Analysis; Multimodality; Guitarricadelafuente; Music Video; Poetics